Interprofessional Education in the Residential Aged Care Setting: A Case Study Approach - Marles, Kirsty; Lawrence, Jennifer; Brewer, Margo; Saunders, Rosemary; Lake, Fiona (Common Ground Publishing, 2012)
In 2009 the Board of Brightwater Care Group supported the development of a pilot Interprofessional Education (IPE) program. The Centre for the Advancement of Interprofessional Education (CAIPE) define IPE as “...those occasions when members (or students) of two or more professions learn with, from, and about one another to improve collaboration and the quality of care.” In the true sense of this definition, Brightwater’s Teaching for the Future Program is designed to give students in their final year of medicine, nursing, pharmacy, dietetics, physiotherapy, speech pathology, and occupational therapy, an opportunity to learn with, from and about one another. Through this program, Brightwater staff are also involved in learning about the different health disciplines, and the benefits reported have included the team working more effectively and efficiently together. The IPE model builds on resident-centric care. The model has been designed to slot into site operations, having links to all areas of operations including: recruitment, training, continuous quality improvement processes, and staff development. Although it is acknowledged that student placements can drain resources, the integration of the IPE program into site operations has resulted in the development of a sustainable, long term program with benefits to residents, staff, the site and the future of IPE. Each student placement varies in length and assessment requirement, however all students undertake the same Interprofessional assessment. The program has to be flexible and dynamic to adapt to the continually changing team make up (not dissimilar to the real health world). The placement is focused around case-based activities which include joint student assessments where students get to explore different communication styles and develop opportunities to work together with other disciplines.